(untitled) (Ameghiniana, 2025)
More than thirty years ago (1989) fossil brood balls of dung beetles (Coprinisphaera) were reported from Antarctica, which were also reconsidered several years later (2006). A recent review of those specimens deposited in the ichnological collection of the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” and of others new specimens collected in December 2015, reveals a probable misinterpretation. The ichnogenicity protocol defined for Mars stick-like structures was tested on the specimens mentioned above to determine whether or not they are true Coprinisphaera. The protocol requires checking morphological regularity, completeness, dispersion, recurrence, complexity, and surface morphology and context. The results show that the tested structures do not fulfill one or more of the requirements of this protocol to be considered as trace fossils and particularly Coprinisphaera. Therefore, Coprinisphaera-like structures from Antarctica are not true trace fossils, consequently the Patagonian specimens remain southernmost recorded so far.